Shattered justice : crime victims' experiences with wrongful convictions and exonerations - Cook, Kimberly J., 1961- (Critical issues in crime and society., 2022)
"Shattered Justice presents original crime victims' experiences with violent crime, investigations and trials, and later exonerations in their cases. Using in-depth interviews with 21 crime victims across the United States, Cook reveals how homicide victims' family members and rape survivors describe the painful impact of the primary trauma, the secondary trauma of the investigations and trials, and then the tertiary trauma associated with wrongful convictions and exonerations. Important lessons and analyses are shared related to grief and loss, and healing and repair. Using restorative justice practices to develop and deliver healing retreats for survivors also expands the practice of restorative justice. Finally, policy reforms aimed at preventing, mitigating, and repairing the harms of wrongful convictions is covered"--